Ibnu Muqlah (W. 328 H): Sejarah dan Sumbangsihnya dalam Penulisan Al-Qur’an - Ali Fitriana Rahmat (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This paper is a brief review of the history of the development of Arabic writing and its contribution to the writing of the Al-Qur'an manuscripts by taking the point of view of a central figure in Arabic writing, Ibn Muqlah (d. 328 H). This article tries to explore the contribution of Ibn Muqlah (d. 328 H) in writing the Al-Qur'an manuscript by tracing the history behind it. Therefore, the preparation of this paper uses a historical approach with a descriptive method of presenting data. The contribution of Ibn Muqlah (d. 328 H) in writing the Qur'an by introducing khaṭ thuluthī and khaṭ naskhī which served as role models for writing the Al-Qur'an manuscripts for centuries.